2020
DOI: 10.3390/cancers12061570
|View full text |Cite
|
Sign up to set email alerts
|

Src Inhibitors Pyrazolo[3,4-d]pyrimidines, Si306 and Pro-Si306, Inhibit Focal Adhesion Kinase and Suppress Human Glioblastoma Invasion In Vitro and In Vivo

Abstract: Glioblastoma (GBM), as the most aggressive brain tumor, displays a high expression of Src tyrosine kinase, which is involved in the survival, migration, and invasiveness of tumor cells. Thus, Src emerged as a potential target for GBM therapy. The effects of Src inhibitors pyrazolo[3,4-d]pyrimidines, Si306 and its prodrug pro-Si306 were investigated in human GBM cell lines (U87 and U87-TxR) and three primary GBM cell cultures. Primary GBM cells were more resistant to Si306 and pro-Si306 according to the 3-(4,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 81 publications
2
23
0
Order By: Relevance
“…In this study, we aimed to evaluate the pro-oxidative effect of Si306 and pro-Si306 in GBM cells. In addition, our earlier studies showed that Si306 and pro-Si306 were twice as efficient in inhibiting GBM cell growth compared to dasatinib and were equally effective in sensitive and multidrug-resistant GBM cells [20,22,25]. We showed that Si306 and pro-Si306 suppress the activity of P-glycoprotein, a membrane efflux transporter whose overexpression is responsible for glioblastoma resistance to therapy and has an important role in the bloodbrain barrier.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…In this study, we aimed to evaluate the pro-oxidative effect of Si306 and pro-Si306 in GBM cells. In addition, our earlier studies showed that Si306 and pro-Si306 were twice as efficient in inhibiting GBM cell growth compared to dasatinib and were equally effective in sensitive and multidrug-resistant GBM cells [20,22,25]. We showed that Si306 and pro-Si306 suppress the activity of P-glycoprotein, a membrane efflux transporter whose overexpression is responsible for glioblastoma resistance to therapy and has an important role in the bloodbrain barrier.…”
Section: Introductionmentioning
confidence: 82%
“…We showed that Si306 and pro-Si306 suppress the activity of P-glycoprotein, a membrane efflux transporter whose overexpression is responsible for glioblastoma resistance to therapy and has an important role in the blood-brain barrier. Si306 and its prodrug also significantly reduced the invasive potential of several primary GBM cultures, as well as GBM xenografts in zebrafish embryo model [25].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Cells in the logarithmic growth stage were inoculated into 96-well plates in groups and performed as described. 17 For The Transwell migration and invasion assay, the Transwell chamber was pretreated with Matrigel (Corning, NY, United States) and dried at 37 C for 1 hour. Other procedures were the same as for the Transwell migration assay.…”
Section: Methodsmentioning
confidence: 99%